(untitled) - Powers, Bob (San Francisco, 2007)
Instructor Excellence guides instructors through a self-assessment to improve their own performance and outlines the performance expectations essential in assessing the success of training. It also includes information to make it easier to write job descriptions, select qualified trainers, establish trainer standards, train new trainers, and develop trainers' careers
Keywords: Employees,Teaching,Teachers,Nhân viên,Giảng dạy,Giáo viên; Training of,Đào tạo